Practices of Procedural Pain Management in Neonates through Continuous Quality Improvement Measures - Jigar P. Thacker; Deep S. Shah; Dipen V. Patel; Somashekhar M. Nimbalkar (International Journal of Pediatrics)
Objective. Although the benefits of pain control measures in neonates are well known, the actual usage was not optimal in our unit. Therefore, we implemented a quality improvement project to improve pain management practices through multiple Plan-Do-Study-Act (PDSA) cycles. Method. Our project included hemodynamically stable newborns weighing ≥1300 g. We identified four common procedures: intravenous cannulation, venous sampling, heel prick, and nasogastric tube insertion. The selected pain control measures were skin-to-skin contact, breastfeeding, expressed breast milk orally, and oral sucrose. Between April 2019 and September 2019, we intervened multiple times and reassessed shortcomings. We encouraged evidence-based practices and gave solutions for shortcomings. Data were interpreted weekly to assess the compliance to pain control interventions. Results. Minimal pain control measures (3-4%) were utilized for identified procedures before the project began. We could improve the use of pain control measures steadily and achieve the target of 80% of procedures after seven different interventions over five months. There was a retention of the effect on reassessing twice at second and fourth months of stopping further intervention once the target got achieved. Conclusion. Quality Improvement science can identify the shortcomings and help to improve the compliance for pain control practices in neonates, as demonstrated in this neonatal unit.